Kinerja Keuangan Berbasis Value Added Menggunakan Konsep EVA, MVA, REVA, FVA, dan SVA pada Perusahaan Semen Kategori Indeks LQ45 - Shalsyabilla Kasandra Midfi; Djoni Djatnika; Fifi Afiyanti Tripuspitorini (Indonesian Journal of Economics and Management, 2021)
The research objective is to examine the financial performance of PT Semen Indonesia (Persero) Tbk (SMGR) and PT Indocement Tunggal Prakarsa Tbk (INTP) 2015-2019. The two companies are companies that are always indexed in the LQ45 stock index in 2015-2019. However, during this period, cement companies experienced excess supply and the emergence of new competitors which would have an effect on the company's financial performance. For this phenomenon, it is required to analyze the value added-based financial performance of the company, in order to determine the company's ability to create added value using the concept of Economic Value Added (EVA), Market Value Added (MVA), Refined Economic Value Added (REVA), Financial Value Added (FVA), and Shareholder Value Added (SVA). The results obtained are that both companies produce fluctuating value added and are not always able to create value added.